2017
DOI: 10.1189/jlb.2a0616-279rrr
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Rho drugs on mast cell activation and degranulation

Abstract: Mast cells are tissue-resident immune cells that produce potent proinflammatory mediators, which are stored in cytoplasmic granules. Stimulation triggers degranulation, a process that mobilizes granules to dock and fuse to the plasma membrane, releasing mediators. Mast cell degranulation has an important role in immunity but can also intensify inflammation and contribute to allergic disorders. Hence, it is important to understand signaling pathways that regulate mast cell degranulation. Here, we examined the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…To gain insight into the factors that govern these cytoskeletal changes, a pharmacological screen of Rho family inhibitors was recently conducted testing the impact of inhibitors of members of the Rho family of GTPases on MC secretion . The results of this study conducted on both FcεRI‐activated BMMCs and RBL cells revealed similar drug sensitivities, therefore implicating similar actin signaling linked with BMMC‐ or RBL‐stimulated exocytosis . These results are consistent with previous studies of direct measurements of actin rearrangements that occur during exocytosis of BMMC or RBL that documented similar actin remodeling …”
Section: Rbl Cells As Reliable Model For Studies On Exocytosissupporting
confidence: 85%
See 2 more Smart Citations
“…To gain insight into the factors that govern these cytoskeletal changes, a pharmacological screen of Rho family inhibitors was recently conducted testing the impact of inhibitors of members of the Rho family of GTPases on MC secretion . The results of this study conducted on both FcεRI‐activated BMMCs and RBL cells revealed similar drug sensitivities, therefore implicating similar actin signaling linked with BMMC‐ or RBL‐stimulated exocytosis . These results are consistent with previous studies of direct measurements of actin rearrangements that occur during exocytosis of BMMC or RBL that documented similar actin remodeling …”
Section: Rbl Cells As Reliable Model For Studies On Exocytosissupporting
confidence: 85%
“…79 The results of this study conducted on both FcεRI-activated BMMCs and RBL cells revealed similar drug sensitivities, therefore implicating similar actin signaling linked with BMMC-or RBL-stimulated exocytosis. 79 These results are consistent with previous studies of direct measurements of actin rearrangements that occur during exocytosis of BMMC or RBL that documented similar actin remodeling. 80,81…”
Section: Rbl Cells As Reliable Model For Studies On Exocytosissupporting
confidence: 54%
See 1 more Smart Citation
“…Studies in our laboratory demonstrated a significant infiltration of mast cells in the lung tissues of asthma mouse model 92 and in nasal eosinophilic polyps of patients with chronic rhinosinusitis with nasal polyps (CRSwNP) 93 . Interestingly, recent studies provided evidence that RhoA signalling is associated with mast cell activation 94 . In particular, Sheshachalam et al 94 showed that RhoA signalling controls mast cell morphology that transitions to an activated form and granule movement for degranulation.…”
Section: Rhoa/rho‐kinase and Airway Inflammationmentioning
confidence: 97%
“…Interestingly, recent studies provided evidence that RhoA signalling is associated with mast cell activation 94 . In particular, Sheshachalam et al 94 showed that RhoA signalling controls mast cell morphology that transitions to an activated form and granule movement for degranulation. Sibilano et al reported a significant impairment in mast cell degranulation in bone marrow‐derived mast cells (BMMCs) with RhoA knockdown 95 .…”
Section: Rhoa/rho‐kinase and Airway Inflammationmentioning
confidence: 99%